2010
DOI: 10.1021/es101374y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Production of Methylmercury within a Stream Channel in Northern California

Abstract: Natural stream ecosystems throughout the world are contaminated by methylmercury, a highly toxic compound that bioaccumulates and biomagnifies in aquatic food webs. Wetlands are widely recognized as hotspots for the production of methylmercury and are often assumed to be the main sources of this neurotoxin in downstream ecosystems. However, many streams lacking wetlands in their drainage basins (e.g., montane and semiarid regions in the western United States) have significant methylmercury contamination, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…11,66,88 Other studies have suggested IHg in streams can be methylated in hyporheic zones 89 or when associated with epilithic periphyton 90 or filamentous algae. 71 Therefore, we suggest it is more likely that in-stream IHg sources and biogeochemical processes in Cache Creek lead to MMHg in the Cache Creek food web.…”
Section: Cache Creekmentioning
confidence: 85%
See 1 more Smart Citation
“…11,66,88 Other studies have suggested IHg in streams can be methylated in hyporheic zones 89 or when associated with epilithic periphyton 90 or filamentous algae. 71 Therefore, we suggest it is more likely that in-stream IHg sources and biogeochemical processes in Cache Creek lead to MMHg in the Cache Creek food web.…”
Section: Cache Creekmentioning
confidence: 85%
“…9-11, 66, 70 Filamentous algae (Spirogyra and Hydrodicton) from Cache Creek had somewhat higher MMHg levels (7 to 83 ng/g, n=4) than Cladoraphora measured in the Yuba River (2.4 to 17 ng/g) 42 but within the range of MMHg reported for various algal groups from the Eel River. 71,72 The %MMHg (mean ±1SD) of organisms changed with general feeding group from filamentous algae (43±19%, n=4) to collector-gatherers and filtering organisms (54±15%, n=10; e.g., Asian clam, caddisfly larva, and burrowing mayfly larva) to predatory invertebrates (92±7%, n=12; e.g., dragonfly larva, damselfly larva, and creeping waterbug) and mosquitofish (82±6%; n=3). This trend is consistent with the preferential trophic transfer of MMHg via biomagnification, as reported previously in Cache Creek (e.g., 11,13 ).…”
Section: Cache Creekmentioning
confidence: 99%
“…Net MeHg production in aquatic ecosystems is linked to environmental and geochemical parameters along with electron donor and acceptor availability (Marvin-DiPasquale et al 2009). Previously, wetlands and floodplain lakes have been associated with MeHg production in aquatic ecosystems, but recent work in stream sediments has found significant in situ MeHg production that warrants further examination of streambed Hg methylation and the associated microbial communi-ties (Tsui et al 2010). Most of the previous work in streams has been performed in anoxic, subsurface sediments and porewater, but MeHg can be produced in surface sediments within the anaerobic microniches in sedimentary biofilms (Bloom et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As we know, MeHg is a more toxic form of Hg and the major risk to the health of humans via consumption of contaminated fish and rice in some Hgcontaminated areas [6,31]. It is well documented that MeHg can be transformed from inorganic Hg in natural waters via biological ways (for example, periphyton [32], plankton produced iodomethane [33], macroalgae [34,35] and especially anoxic bacteria such as sulfate-reducing bacteria [36] in deep and littoral sediments are found to produce methylated mercury) and non-biological ways [37] (such as methyltin, methylcobalamin and humic matter in sediments). In order to verify the production of MeHg when P. tricornutum was exposed to HgCl 2 , we detected and identified MeHg in both the intracellular extract of P. tricornutum and the corresponding culture solution using HPLC-AFS and GC-MS. MeHg was detected in the P. tricornutum culture solutions using HPLC-AFS ( Figure 6(b)) strictly following the MeHg extraction protocols [21], but no MeHg was detected in the control culture solutions containing no P. tricornutum.…”
Section: Transformation Of Hg Inside P Tricornutummentioning
confidence: 99%